The effects of conversion of lands to the agricultural sector of Plaridel, Bulacan - Alcaide, Allen N.; Sebastian, Charito Imperial (Pampanga University of the Philippines Diliman Extension Program in Pampanga, 2015)
This study explored the effects of land use conversion to the agricultural sector specifically tot he socioeconomic status of farmer-landowners and to the economic development of the Municipality of Plaridel in the province of Bulacan through the use of mixed media method-quantitative and qualitative. The respondents involved in this research were farmer-landowners who sold their agricultural land for industrial use in Plaridel, Bulacan. A survey questionnaire was distributed to 29 respondents, obtaining information on the cause and effects of their decision in selling their land. Furthermore, available statistical data relevant to the study were obtained from the Department of Agrarian Reform and Department of Agriculture. Results suggest that the conversion of lands has a positive effect on the municipality's food sustainability since the level of productivity of remaining lands improved despite of the decline in the number of irrigated lands. Also, the paper finds that the landowners affected by the conversion process are satisfied with the compensation and its influence on their quality of life.
Thesis (Business Economics) UPDEPP, 2015
Keywords: Land use -- Economic aspects -- Philippines; Farms -- Economic aspects -- Philippines